Optimizing noisy galvanic vestibular stimulation (nGVS) for postural control: methodological considerations when individualizing the signal for people with bilateral vestibulopathy - McLaren, Ruth; Smith, Paul F.; Taylor, Rachael L.; Taylor, Denise (Frontiers in Neurology, 2025)
An established aspect of noisy galvanic vestibular stimulation (nGVS) is tuning the nGVS signal to optimize stability on an individual basis. However, conventional tuning methods are strongly influenced by historical approaches and fail to integrate contemporary research findings. We outline a process used to integrate current physiological and neuroscientific insights into a robust method for personalizing nGVS signals to improve stability. We argue that an optimization protocol for a neuromodulatory nGVS signal designed to facilitate postural control needs to include: (1) A task that is relevant to the population, and which can be modified to give an appropriate level of challenge at an individual level; (2) Elements that can be reliably measured and are responsive to changes in postural control; (3) Well controlled and defined signal parameters; (4) Potential to be translated into the clinical setting. Questioning conventional methods enabled us to develop an alternative nGVS optimization assessment to enhance postural control in people with bilateral vestibulopathy. Refining this optimization assessment represents a crucial step in developing individualized nGVS interventions. The fundamental principles applied to develop our method can be adapted to other neuromodulatory stimuli across different impairments and populations.